Highly-dispersive spin gapless semiconductors in rare-earth-element contained quaternary Heusler compounds. (9th February 2017) - Xu, Guizhou; You, Yurong; Gong, Yuanyuan; Liu, Er; Xu, Feng; Wang, Wenhong
Abstract: The acquisition of high mobility electrons in the zero-gap band of spin gapless semiconductors is crucial for their practical applications in spintronic devices. In this work, we propose to design a higher dispersive band by importing the rare-earth atom into the Heusler compounds. With first principles calculations, we identify several new spin gapless semiconductor candidates in the 21-electron LiMgPdSn-type quaternary Heusler alloys of (Y, La, Lu)CoCr/FeMn(Al, Ga). Densities of states for most of them reveal large band gaps in the minority spin direction, and relatively low states near the Fermi level in the majority spin. According to the electron projected band analysis, we find the import of the rare earth atom can enhance the sp component in the band across the Fermi level, which is conducive to form a linear-dispersive band that is promising to enhance the carrier mobility of spin gapless semiconductors.